Функціоналізація оксимів (спіро)піранокумаринів - Красилов, І.В.; Москвіна, В.С.; Хиля, В.П. (Доповіді НАН України, 2023)
Досліджено шляхи структурної модифікації оксимів піранокумаринів та спіропіранокумаринів — синтетичних аналогів природного гравеолону. Показано, що оксими (спіро)піранокумаринів є зручними реагентами для введення додаткових функціональних груп — аміногрупи, гідроксильної групи, амідоксимного фрагмента — біоізостера карбоксильної функції, а також оксадіазольного циклу. Розроблено препаративні методики алкілювання оксимів (спіро)піранокумаринів і досліджено взаємодію отриманих похідних з первинними алкіламінами, гідроксиламіном та триетилортоформіатом. This study focuses on the structural modification of oximes of pyranocoumarins and spiropyranocoumarins – synthetic analogues of the naturally occurring compound graveolone. It has been demonstrated that oximes of (spiro)pyranocoumarins serve as convenient reagents for the introduction of additional functional groups, such as amino groups, hydroxyl groups, amidoxime fragments (bioisosteres of carboxyl functions), and oxadiazole rings. Preparative methods for the alkylation of oximes of (spiro)pyranocoumarins were developed, and the interaction of the resulting derivatives with primary alkylamines, hydroxylamine, and triethylorthoformate was investigated.